Technology, needs and power as means of distribution and justice - Ángel García B. (Universidad Central de Venezuela, 2006)
This paper provides a review of the philosophical traditions on the study of social inequality and recent theories of justice. On the one hand, it sets forth the fundamental ideas of those philosophers who have been labeled as conservative or functionalists and have defended inequality as something which is expected to be just and inevitable. On the other hand, it presents, as well, the ideas of those philosophers known as radicals who state not only that social inequality is unjust, but rather that it is evitable as well. Subsequently, the paper describes the main ideas concentrated in what Lenski (1993) calls the growing dialectic synthesis of the theory of social stratification which incorporates elements from both traditions. The paper reviews the theories of distribution based on the principles of political economy proposed by the classical economists, and contrasts them with those proposed by the marginalist theory and the theory of social stratification. In doing so, the paper briefly considers the relationship between technology, and political instruments of distribution such as needs, power and privileges. Regarding the recent theories of justice, the paper mainly focuses on the proposals of Rawls (1971) and Nozick (1974). Finally, with respect to the current state of affairs, the roles of information-based technology and modern post-Bretton Woods financial institutions are briefly discussed -in terms of their complementarities- to explain the well known persistent increase in global social inequality.